PENGARUH PRODUKSI, KURS DOLLAR AMERIKA, SUKU BUNGA KREDIT TERHADAP EKSPOR KAKAO DAN PERTUMBUHAN EKONOMI INDONESIA - Rustiana Dewi, Ni Putu Linda; Kartika, I Nengah; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 5 (2021): VOL 10 NO 5, MEI 2021 (1774 - 2222), 2021)
Indonesia one of the countries that have large plantation products. One of Indonesia's mainstay plantations cocoa. In this study the objectives, namely 1) to analyze the effect of production, the US dollar exchange rate and credit interest rates Indonesian cocoa exports; 2) analyze the effect of production, the US dollar exchange rate and lending rates Indonesia's economic growth; 3) to analyze the effect of production, the US dollar exchange rate and credit interest rates on economic growth through Indonesian cocoa exports. This study uses secondary data located in Indonesia in the period 1988-2017 using path analysis techniques. The results showed that 1) the production and the exchange rate of the US dollar had a positive and significant effect while lending rates had a negative and significant effect on cocoa exports, 2) the production, the US dollar exchange rate, and cocoa exports had a positive and significant effect while the lending rates had a negative and significant effect on Indonesia's economic growth, 3) cocoa exports are intervening variables of the effect of production, the US dollar exchange rate and credit interest rates on Indonesia's economic growth. Keywords: production, United States dollar exchange rate, credit interest rates, cocoa exports, and economic growth.